Large Group Teaching in the Medical Colleges of Dhaka City - Mohammad, S; Muazzam, N; Hanif, A; Talukder, HK; Hossain, MZ; Nahar, N (Journal of Dhaka Medical College, 2010)
This descriptive type of cross sectional study was conducted with the objective to study quality of current practices of large group teaching in selected medical colleges. This study was conducted at different government and non government medical colleges in the year 2007 adopting the convenient sampling using a checklist filled up by participatory observation at 36 lecture classes. The study revealed that the characteristics of the effective lecture are not strictly maintained in the present lecture classes in the medical colleges. Although due to time constraint the study was conducted at limited measure. The study reveals that more than thirty percent of the teachers did not attend any teaching methodology course. The medical colleges are lack in instructional media. More than twenty-seven percent teachers did not mention objectives at the beginning of the lecture. During informal interview some teachers expressed that mentioning objectives at the beginning is wastage of time. Some teacher's expressed that these methodologies of western culture do not fit in the context of Bangladesh due to limited resources, shortage of manpower and over crowding of students. More than eleven percent teachers did not use any visual aid and more than half of the teachers used visual that could not be read from the last bench. Fifty percent of the aid medical teachers do not summarize their lecture at the end. In seventeen percent lecture classes, the students only opened their mouth to respond to the attendance call. The study recommended that all the medical teachers should attend the teaching methodology course as a must. There should be regular visit to the medical colleges lecture galleries informally by authority concerned to ensure the required facilities of lecture classes. Students' evaluation, lecturers' self-rating may really trigger the teachers to identify their deficiencies, and can make real difference. Institute should ensure that teachers are given the support necessary for them to function effectively. Essential audiovisual support should be provided to the teachers for effective delivery of lecture. Key words: Large group teaching; medical college. DOI: 10.3329/jdmc.v18i1.6302 J Dhaka Med Coll. 2009; 18(1) : 28-32